ALOKASI OPTIMUM DAN WILAYAH PENGEMBANGAN PERIKANAN BERBASIS ALAT TANGKAP POTENSIAL DI TELUK JAKARTA - Siti Radarwati; Mulyono S. Baskoro; Daniel R. Monintja; A. Purbayanto (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2010)
Jakarta Bay and its neighbouring waters of Seribu Islands are categorized as fullly exploited water areas which theirs coastal areas accomodate multifunction services. Therefore, it needs precautionary approach to manage fisheries activity in that locations. The objectives of this study are to determine optimum allocation of fishing gears and fisheries development areas based on potential fishing gears in Jakarta Bay. The methods used in this study are Linear Goal Programming (LGP) and Locations Quotient (LQ). The result revealed that the potential fishing gears to be developed were pelagic danish seine, drift gillnet, boat lift net, set bottom long line, portable trap and muroami which have the optimum allocation for each fishing gear; 7 units, 98 units, 23 units, 18 units, 8547 units, and 798 units. The potential fishing gears for pelagic danish seine could be developed in Penjaringan and North Seribu Island Districts; drift gillnet could be developed in Cilincing District; boat lift net could be developed in Penjaringan District; set bottom long line could be developed in Penjaringan District; portable trap could be developed in Cilincing and South Seribu Island Districts while muroami could be developed in Penjaringan and South Seribu Island Districts.